MARKETING STRATEGY ANALYSIS OF LEATHER CRAFT PRODUCTS IN UD. IRWAN JAYA IN THE TIME OF COVID-19 WITH SWOT METHODS and QSPM - Noviawan, Rachmat; Ismiyah, Elly; Fathoni, M. Zainuddin (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
UD. Irwan Jaya is one of the SME leather craftsmen in Putat Village, Kebomas District, Gresik Regency and has been in this business for approximately 30 years. From this leather, the goods that the UKM can produce are wallets and bags. Based on the results of an interview with Mr. Irwan as the business owner, current sales conditions tend to decline in a few months in July 2020 - May 2021. This is influenced by the COVID-19 outbreak that has hit almost the entire world, affecting several industrial sectors including SMEs in the city of Gresik as well. experienced a decrease in the level of sales so that the profits that can be obtained are only around 7% within 1 month (Narto & Gatot, 2020). This condition requires the selection of a marketing strategy through the identification of the internal and external factors of SMEs. The selection of this strategy aims to improve and develop SMEs so that they can survive in uncertain conditions, so that in the preparation and formulation of the marketing strategy, a scientific approach will be used in the form of integration of the IFE-EFE Matrix SWOT method and QSPM (Quantitative Strategic Planning Matrix). SWOT analysis is based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats (Rangkuti, 2005). The next step is to determine strategic priorities from several alternatives resulting from the SWOT analysis using the QSPM method. From the results of the SWOT analysis, the company's position is in cell V, namely the hold and mountain strategy and gets 8 strategies, then determines the prioritized strategy using QSPM. The prioritized strategy is the strategy of creating an online store as a technology in business